Competências gerenciais essenciais requeridas e praticadaspelos gestores: estudo em empresas do pólo industrial de Manaus-Amazonas - Paulo Cesar Diniz de Araujo (2014)
The study aimed to identify the Essential Management Skills Required Practices and by the managers of the Industrial Pole of Manaus (PIM) for performance management function. This theme is part of the contemporary debate about the necessary competitiveness and continuous search of quality in new products and services, requiring organizations, managers can respond to these demands through the accumulation of new knowledge and skills. To that end, we adopted as a methodological strategy was quantitatively oriented research design, using internet survey with the leaders and managers of companies located in the study area. After mapping the universe came to a set of 96 respondents who addressed issues related to Socio-demographic results, Professionals, Institutional and on the lifting of Management Skills, Leadership, Decision Making, Communication, Organizational Strategy, Business Management, Innovation, Technology and Adaptability. After being held different analyzes of statistical within what is advocated in the literature, the results point allowed the expertise deemed most important by managers suggesting the need to plan and direct investments in management development, either by the managers themselves PIM, is by organizations or by educational institutions offering executive education based on managerial skills essences for managers working in this Brazilian industrial region.